2004
DOI: 10.1002/pen.20257
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on radial extrudate swell and velocity profiles of flowing PS melt in an electro‐magnetized die of an extrusion rheometer

Abstract: This article investigates the radial extrudate swell and velocity profiles of polystyrene melt in a capillary die of a constant shear‐rate extrusion rheometer, using a parallel coextrusion technique. An electro‐magnetized capillary die was used to monitor the changes in the radial extrudate swell profiles of the melt, which is relatively novel in polymer processing. The magnetic flux density applied to the capillary die was varied in a parallel direction to the melt flow, and all tests were performed under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…For a given roller speed, the drawdown force decreased with increasing die temperature due to an increase in viscous deformation and molecular mobility of the LDPE melt. [24] The effect of number of extrusion passes for all die temperatures was similar to that discussed relative to Fig. 4c.…”
Section: Mechanical Properties Of Molten Ldpementioning
confidence: 65%
“…For a given roller speed, the drawdown force decreased with increasing die temperature due to an increase in viscous deformation and molecular mobility of the LDPE melt. [24] The effect of number of extrusion passes for all die temperatures was similar to that discussed relative to Fig. 4c.…”
Section: Mechanical Properties Of Molten Ldpementioning
confidence: 65%
“…The mechanism for the magnetic field effect on the degree of crystallinity was associated with a large diamagnetic anisotropy of the benzene molecules within the PEEK molecules, which resulted in the magnetic torque acting on the polymer molecules. The magnetic torque, occurring as a result of the motion of the existing electrons and distortions of the electron clouds within the benzene rings within the PEEK molecules, can be sufficiently large to induce appreciable orientation and alignment of the molecules [28,29]. If so, the molecular configuration and alignment changes of the melt while coated on the substrate, to some extent, would change, and this led to the changes in molecular crystallization during the cooling.…”
Section: Effect Of Magnetic Fieldmentioning
confidence: 95%
“…In addition, current research has also found that the magnetic field has a direct impact on the swelling property of melt polymer. Sombatsompop et al [3][4][5] studied the effect of the electrical magnetic field on the swell property of melt polymer by designing and constructing an electro-magnetic die with adjustable magnetic density. Their study found that the extrudate swell of polymer increased with the increase of magnetic flux density, particularly polymer with benzene as repeating unit in its molecular chain, such as polystyrene (PS).…”
Section: Introductionmentioning
confidence: 99%